Multi-crosslinking network temperature-resistant and salt-resistant pre-crosslinking gel particle as well as preparation method and application of multi-crosslinking network temperature-resistant and salt-resistant pre-crosslinking gel particle
By preparing pre-crosslinked gel particles with multiple crosslinked networks, the problem of insufficient plugging strength in high-temperature and high-salt reservoir environments was solved, achieving effective plugging under high-temperature and high-salt conditions and improving oilfield recovery.
Patent Information
- Application Number
- CN202411680970.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-11-22
AI Technical Summary
Existing pre-crosslinked gel particles are difficult to maintain effective sealing performance in high-temperature and high-salinity reservoir environments, which affects oilfield recovery.
Pre-crosslinked gel particles with temperature and salt resistance were prepared by using raw materials such as acrylamide, trans-resveratrol, triphenylethylphenol polyoxyethylene ether methacrylate and aldehyde cellulose nanofibers to form a multi-linked network through initiator crosslinking.
The prepared pre-crosslinked gel particles can still maintain high plugging strength and toughness under high temperature of 130℃ and mineralization of 250,000 mg/L, which improves the oilfield recovery rate.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of oil and gas field development, and in particular to a multi-crosslinked network temperature-resistant and salt-resistant pre-crosslinked gel particle and a preparation method and application thereof. Background Art
[0002] More than 80% of my country's onshore oil fields are developed by water injection, but the water drive recovery rate is generally low, usually less than 50%. Reservoir heterogeneity is one of the important factors affecting the recovery of water-driven oil reservoirs. Due to the difference in permeability of the reservoir itself, the injected water can easily penetrate along the high permeability layer, fractures, large pores and other advantageous channels, resulting in ineffective circulation of the injected water, which seriously affects the economic benefits of the oil field.
[0003] Chemical profile control and water plugging is an effective way to improve the effect of water injection development in oil fields and achieve stable production of oil reservoirs. Chemical profile control agents are used to plug the dominant channels of water injection wells, reduce the amount of water absorbed by the dominant channels, and increase the water drive sweep coefficient, thereby increasing the oil recovery rate. Pre-crosslinked gel particles are widely used due to their simple process, low price, high plugging strength and long effective period.
[0004] For example, Chinese patent CN202311392830.9 discloses a gel particle profile control agent for plugging oil layer in oil field water drive, which is prepared by adding chromium crosslinking agent, reinforcing agent and gel promoter to partially hydrolyzed polyacrylamide. The gel particle profile control agent has high plugging strength. However, facing the increasingly complex reservoir environment (temperature>100℃, mineralization>100,000), the above-mentioned pre-crosslinked gel particles are difficult to apply. Summary of the invention
[0005] The purpose of the present invention is to provide a multi-crosslinked network temperature-resistant and salt-resistant pre-crosslinked gel particle and a preparation method and application thereof. The pre-crosslinked gel particle has high salt resistance and high strength and can withstand a high temperature of at least 130°C.
[0006] The present invention first provides a pre-crosslinked gel particle. The raw materials for preparing the pre-crosslinked gel particle include acrylamide, trans-resveratrol, triphenyl ethylphenol polyoxyethylene ether methacrylate, aldehyded cellulose nanofibrils and an initiator.
[0007] The pre-crosslinked gel particles described above include, by weight, 15 to 20 parts of acrylamide, 0.4 to 1.5 parts of trans-resveratrol, 4.3 to 5 parts of triphenyl phenol polyoxyethylene ether methacrylate, and 1.8 to 3.5 parts of aldehyded cellulose nanofibrils; The mass of the initiator is 0.01% to 0.05% of the total mass of the monomers, specifically 0.011%, 0.012% or 0.016%; wherein the total mass of the monomers is the sum of the masses of acrylamide, trans-resveratrol, triphenyl phenol polyoxyethylene ether methacrylate and aldehyded cellulose nanofibrils.
[0008] In the above-mentioned pre-crosslinked gel particles, the raw materials also include water; based on the total mass fraction of the monomer and water being 100 parts, the remainder is water; The monomers are acrylamide, trans-resveratrol, triphenyl ethylphenol polyoxyethylene ether methacrylate and aldehyded cellulose nanofibrils.
[0009] The raw materials for preparing the above-mentioned pre-crosslinked gel particles are any of the following: 1) 18 parts of acrylamide, 0.5 parts of trans-resveratrol, 4.5 parts of triphenyl phenol polyoxyethylene ether methacrylate, 2 parts of aldehyded cellulose nanofibrils, and 75 parts of water; the mass of the initiator is 0.012% of the total mass of the monomers; 2) 17 parts of acrylamide, 1 part of trans-resveratrol, 4.5 parts of triphenylphenol polyoxyethylene ether methacrylate, 2.5 parts of aldehyded cellulose nanofibrils, and 75 parts of water; the mass of the initiator is 0.012% of the total mass of the monomers; 3) 18 parts of acrylamide, 1.5 parts of trans-resveratrol, 5 parts of triphenyl phenol polyoxyethylene ether methacrylate, 3.5 parts of aldehyded cellulose nanofibrils, and 72 parts of water; the mass of the initiator is 0.011% of the total mass of the monomers; 4) 17 parts of acrylamide, 1 part of trans-resveratrol, 4.5 parts of triphenyl phenol polyoxyethylene ether methacrylate, 2.5 parts of aldehyded cellulose nanofibrils, and 75 parts of water; the mass of the initiator is 0.016% of the total mass of the monomers.
[0010] In the above-mentioned pre-crosslinked gel particles, the initiator is a persulfate, and specifically may be ammonium persulfate.
[0011] In the above-mentioned pre-crosslinked gel particles, the preparation method of the hydroformylated cellulose nanofibrils comprises the following steps: mixing the cellulose nanofibrils, periodate and a solvent for reaction, and the obtained solid is the hydroformylated cellulose nanofibrils.
[0012] In the above-mentioned pre-crosslinked gel particles, the reaction is carried out under light-proof conditions at a temperature of 40-50° C. for 3-4 hours; The pH of the reaction solution was adjusted to 5-6 to carry out the reaction.
[0013] Specifically, hydrochloric acid can be used to adjust the pH of the reaction solution.
[0014] In the above-mentioned pre-crosslinked gel particles, the periodate is at least one of sodium periodate and potassium periodate; The solvent is water; The mass ratio of the cellulose nanofibrils to periodate is 10:1.5-2.5; The mass of the cellulose nanofibrils is 3-5 wt % of the total mass of the cellulose nanofibrils and the solvent.
[0015] In the above-mentioned pre-crosslinked gel particles, the method for preparing the hydroformylated cellulose nanofibrils further comprises the steps of washing the solid phase with water to neutrality and drying after the reaction.
[0016] Furthermore, the present invention also provides a method for preparing the above-mentioned pre-crosslinked gel particles, comprising the following steps: Acrylamide, trans-resveratrol, aldehyded cellulose nanofibrils and triphenyl phenol polyoxyethylene ether methacrylate are dispersed in water, and an initiator is added under deoxygenated conditions to react to obtain the pre-crosslinked gel particles.
[0017] In the above preparation method, the reaction temperature is 50-60°C; the reaction time is 3-5h; Use nitrogen to deoxygenate; The preparation method also includes the steps of granulating, drying and crushing the obtained pre-crosslinked gel after the reaction.
[0018] Finally, the present invention provides the use of the pre-crosslinked gel particles as a profile control and water plugging agent in improving the recovery rate of oil and gas fields.
[0019] Specifically, the formation temperature of the oil and gas field is 100-130°C; the formation water salinity is 10×10 4 mg / L~25×10 4 mg / L.
[0020] More specifically, the formation temperature of the oil and gas field is 130°C; the formation water salinity is 25×10 4 mg / L.
[0021] The present invention has the following advantages: (1) The pre-crosslinked gel particles of the present invention have high salt resistance and temperature resistance and can withstand a mineralization degree of at least 25×10 4 mg / L, temperature at least 130°C; (2) The pre-crosslinked gel particles of the present invention are heated to 130°C and have a mineralization degree of 25×10 4 mg / L, and it still maintains a high steering pressure after aging for 50 days under the condition of calcium ion concentration of 5000 mg / L; the toughness coefficient after aging for 50 days is greater than 0.9, indicating that it has good toughness. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The expansion multiples of the multi-crosslinked network temperature-resistant and salt-resistant pre-crosslinked gel particles prepared in Example 1 at different temperatures.
[0023] Figure 2 The expansion multiples of the multi-crosslinked network temperature-resistant and salt-resistant pre-crosslinked gel particles prepared in Example 2 at different temperatures.
[0024] Figure 3 The expansion multiples of the multi-crosslinked network temperature-resistant and salt-resistant pre-crosslinked gel particles prepared in Example 3 at different temperatures.
[0025] Figure 4 The expansion multiples of the multi-crosslinked network temperature-resistant and salt-resistant pre-crosslinked gel particles prepared in Example 4 at different temperatures.
[0026] Figure 5 The expansion multiples of the multi-crosslinked network temperature-resistant and salt-resistant pre-crosslinked gel particles prepared in Example 1 at different mineralization degrees.
[0027] Figure 6 The expansion multiples of the multi-crosslinked network temperature-resistant and salt-resistant pre-crosslinked gel particles prepared in Example 2 at different mineralization degrees.
[0028] Figure 7 The expansion multiples of the multi-crosslinked network temperature-resistant and salt-resistant pre-crosslinked gel particles prepared in Example 3 at different mineralization degrees.
[0029] Figure 8 The expansion multiples of the multi-crosslinked network temperature-resistant and salt-resistant pre-crosslinked gel particles prepared in Example 4 at different mineralization degrees.
[0030] Fig. 9 The turning pressures of the multi-crosslinked network temperature-resistant and salt-resistant pre-crosslinked gel particles prepared in Examples 1 to 4 at the initial stage and at different aging times.
[0031] Fig.10 It is the toughness index of the multi-crosslinked network temperature-resistant and salt-resistant pre-crosslinked gel particles prepared in Examples 1 to 4. Tool Implementation Method The present invention is further described in detail below in conjunction with specific embodiments. The given examples are only for illustrating the present invention, but not for limiting the scope of the present invention.
[0032] The experimental methods in the following examples are all conventional methods unless otherwise specified.
[0033] The quantitative tests in the following examples were all repeated three times, and the results were averaged.
[0034] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.
[0035] The cellulose nanofibrils used in the following examples were purchased from Northern Century (Jiangsu) Cellulose Materials Co., Ltd.
[0036] Example 1 The multi-crosslinked network temperature-resistant and salt-resistant pre-crosslinked gel particles of this embodiment are made of the following raw material components: 18g acrylamide, 0.5g trans-resveratrol, 4.5g triphenyl phenol polyoxyethylene ether methacrylate, 2g aldehyded cellulose nanofibrils, 0.003g ammonium persulfate and 75g deionized water.
[0037] The specific preparation method is as follows: (1) Preparation of aldehyded cellulose nanofibrils: 4 g of cellulose nanofibrils were added to 96 mL of water, followed by 0.8 g of sodium periodate. The temperature was raised to 45 °C with continuous stirring, and the pH of the reaction solution was adjusted to 5 with hydrochloric acid. The reaction was allowed to proceed for 3.5 h in the dark. After the reaction was completed, the solid phase was collected by centrifugation and washed with water until it was neutral, and then dried in a vacuum.
[0038] (2) Preparation of pre-crosslinked gel particles: Add 0.5 g of trans-resveratrol and 4.5 g of triphenylethylphenol polyoxyethylene ether methacrylate to 75 g of deionized water and sonicate until the solution is uniform; then add 18 g of acrylamide and 2 g of aldehyded cellulose nanofibrils to the above solution and stir until the solution is uniform; introduce N2 for 30 min to remove oxygen in the solution and air in the flask; add 0.003 g of ammonium persulfate and stir evenly, continue to introduce N2 for 30 min, heat the system to 50°C and keep warm for 3 h to obtain a gel particle block product, and after granulation, drying, crushing and screening, obtain multi-crosslinked network temperature-resistant and salt-resistant pre-crosslinked gel particles.
[0039] Example 2 The multi-crosslinked network temperature-resistant and salt-resistant pre-crosslinked gel particles of this embodiment are made of the following raw material components: 17g acrylamide, 1g trans-resveratrol, 4.5g triphenyl phenol polyoxyethylene ether methacrylate, 2.5g aldehyded cellulose nanofibrils, 0.003g ammonium persulfate, and 75g deionized water.
[0040] The specific preparation method is as follows: (1) Preparation of aldehyded cellulose nanofibrils: 3.8 g of cellulose nanofibrils were added to 96 mL of water, followed by 0.68 g of sodium periodate. The temperature was raised to 45 °C with continuous stirring, and the pH of the reaction solution was adjusted to 5 with hydrochloric acid. The reaction was allowed to proceed for 3.5 h in the dark. After the reaction was completed, the solid phase was collected by centrifugation and washed with water until it was neutral, and then dried in a vacuum.
[0041] (2) Preparation of pre-crosslinked gel particles: Add 1 g of trans-resveratrol and 4.5 g of triphenylethylphenol polyoxyethylene ether methacrylate to 75 g of deionized water and sonicate until the solution is uniform; then add 17 g of acrylamide and 2.5 g of aldehyded cellulose nanofibrils to the above solution and stir until the solution is uniform; introduce N2 for 30 min to remove oxygen in the solution and air in the flask; add 0.003 g of ammonium persulfate and stir evenly, continue to introduce N2 for 30 min, heat the system to 50°C and keep warm for 3 h to obtain a gel particle block product, and after granulation, drying, crushing and screening, obtain multi-crosslinked network temperature-resistant and salt-resistant pre-crosslinked gel particles.
[0042] Example 3 The multi-crosslinked network temperature-resistant and salt-resistant pre-crosslinked gel particles of this embodiment are made of the following raw material components: 18g acrylamide, 1.5g trans-resveratrol, 5g triphenyl phenol polyoxyethylene ether methacrylate, 3.5g aldehyded cellulose nanofibrils, 0.003g ammonium persulfate, and 72g deionized water.
[0043] The specific preparation method is as follows: (1) Preparation of aldehyded cellulose nanofibrils: 4.2 g of cellulose nanofibrils were added to 96 mL of water, followed by 0.97 g of sodium periodate. The temperature was raised to 45 °C under continuous stirring, and the pH of the reaction solution was adjusted to 6 with hydrochloric acid. The reaction was carried out in a dark environment for 4 h. After the reaction was completed, the solid phase was collected by centrifugation, washed with water until neutral, and then dried in a vacuum.
[0044] (2) Preparation of pre-crosslinked gel particles: Add 1.5 g of trans-resveratrol and 5 g of triphenylethylphenol polyoxyethylene ether methacrylate to 72 g of deionized water and sonicate until the solution is uniform; then add 18 g of acrylamide and 3.5 g of aldehyded cellulose nanofibrils to the above solution and stir until the solution is uniform; introduce N2 for 30 min to remove oxygen in the solution and air in the flask; add 0.003 g of ammonium persulfate and stir evenly, continue to introduce N2 for 30 min, heat the system to 50°C and keep warm for 3 h to obtain a gel particle block product, and after granulation, drying, crushing and screening, obtain multi-crosslinked network temperature-resistant and salt-resistant pre-crosslinked gel particles.
[0045] Example 4 The multi-crosslinked network temperature-resistant and salt-resistant pre-crosslinked gel particles of this embodiment are made of the following raw material components: 17g acrylamide, 1g trans-resveratrol, 4.5g triphenylphenol polyoxyethylene ether methacrylate, 2.5g aldehyded cellulose nanofibrils, 0.004g ammonium persulfate, and 75g deionized water.
[0046] The specific preparation method is as follows: (1) Preparation of aldehyded cellulose nanofibrils: 4 g of cellulose nanofibrils were added to 96 mL of water, followed by 0.8 g of sodium periodate. The temperature was raised to 45 °C with continuous stirring, and the pH of the reaction solution was adjusted to 5 with hydrochloric acid. The reaction was allowed to proceed for 3.5 h in the dark. After the reaction was completed, the solid phase was collected by centrifugation and washed with water until it was neutral, and then dried in a vacuum.
[0047] (2) Preparation of pre-crosslinked gel particles: Add 1 g of trans-resveratrol and 4.5 g of triphenylethylphenol polyoxyethylene ether methacrylate to 75 g of deionized water and sonicate until the solution is uniform; then add 17 g of acrylamide and 2.5 g of aldehyded cellulose nanofibrils to the above solution and stir until the solution is uniform; introduce N2 for 30 min to remove oxygen in the solution and air in the flask; add 0.004 g of ammonium persulfate and stir evenly, continue to introduce N2 for 30 min, heat the system to 60°C and keep warm for 4 h to obtain a gel particle block product, and after granulation, drying, crushing and screening, obtain multi-crosslinked network temperature-resistant and salt-resistant pre-crosslinked gel particles.
[0048] Embodiment 5, performance test 1. Expansion test The multi-crosslinked network heat-resistant and salt-resistant pre-crosslinked gel particles prepared in Examples 1 to 4 were taken, and their weight changes under different temperatures and different mineralization conditions were tested by weighing method, and then the mass expansion multiple was calculated according to the weight change. The final result is as follows: Figure 1 to Figure 8 shown.
[0049] Figure 1~Figure 4 It is mainly used to test the temperature resistance of pre-crosslinked gel particles: the pre-crosslinked gel particles are placed in a temperature range of 25×10 4 mg / L of water, of which the calcium ion concentration is 5000mg / L, and the rest are sodium ions and chloride ions; its temperature resistance under high salt conditions is tested by changing the temperature. Figure 1~Figure 4 It can be seen that with the increase of temperature, the expansion multiple of the pre-crosslinked gel particles increases, and they are still not dehydrated after aging for 50 days.
[0050] Figure 5~Figure 8 It is mainly used to test the salt resistance of pre-crosslinked gel particles: the pre-crosslinked gel particles are placed in water at a temperature of 130°C, and the mineralization of the water is changed (water of any mineralization contains 5000mg / L of calcium ions, and the rest are sodium ions and chloride ions). By changing the mineralization, its salt resistance under high temperature conditions is tested. Figure 5~Figure 8 It can be seen that with the decrease of mineralization, the expansion multiple of gel particles increases rapidly, and they are still not dehydrated after aging for 50 days.
[0051] Depend on Figure 5-Figure 8It can be seen that the pre-crosslinked gel particles prepared in the embodiment of the present invention can withstand a mineralization degree of at least 25×10 4 mg / L, and the temperature is at least 130°C, and it has strong resistance to heat and salt.
[0052] 2. Pre-crosslinked gel particle strength test Steering pressure method: Take the pre-crosslinked gel particles prepared in Examples 1 to 4, let them pass through a 180-mesh screen at a certain speed, and record the maximum pressure P1 when the pre-crosslinked gel particle system passes through the screen. Collect the pre-crosslinked gel particle system after passing through, let it pass through the screen again at the same speed, and record the maximum pressure P2 when passing through. The toughness index is defined as the ratio of P2 to P1. The closer the toughness index is to 1, the better the toughness. The specific method is as follows: At a temperature of 130°C, use a mineralization degree of 25×10 4 The pre-crosslinked gel particles prepared in Examples 1 to 4 were prepared into a suspension with a mass concentration of 0.5%, and the steering pressure at the initial stage and at different aging times was tested. The test results are shown in FIG. Fig. 9 and Fig.10 shown.
[0053] Depend on Fig. 9 and Fig.10 It can be seen that the multi-crosslinked network heat-resistant and salt-resistant pre-crosslinked gel particles prepared in Examples 1-4 still maintain a high turning pressure and strength after aging for 50 days. The toughness coefficient after aging for 50 days is greater than 0.9, indicating that the multi-crosslinked network heat-resistant and salt-resistant pre-crosslinked gel particles have good toughness.
Claims
1. A pre-crosslinked gel particle, characterized in that: The raw materials for preparing the pre-crosslinked gel particles include acrylamide, trans-resveratrol, triphenyl ethylphenol polyoxyethylene ether methacrylate, aldehyded cellulose nanofibrils and an initiator.
2. The pre-crosslinked gel particles according to claim 1, characterized in that: By weight, 15-20 parts of acrylamide, 0.4-1.5 parts of trans-resveratrol, 4.3-5 parts of triphenyl phenol polyoxyethylene ether methacrylate, and 1.8-3.5 parts of aldehyded cellulose nanofibrils; The mass of the initiator is 0.01% to 0.05% of the total mass of the monomers; wherein the total mass of the monomers is the sum of the masses of acrylamide, trans-resveratrol, triphenyl phenol polyoxyethylene ether methacrylate and aldehyded cellulose nanofibrils.
3. The pre-crosslinked gel particles according to claim 1 or 2, characterized in that: The raw materials also include water; Taking the total weight of monomer and water as 100 parts, the balance is water; The monomers are acrylamide, trans-resveratrol, triphenyl ethylphenol polyoxyethylene ether methacrylate and aldehyded cellulose nanofibrils.
4. The pre-crosslinked gel particles according to any one of claims 1 to 3, characterized in that: The initiator is persulfate.
5. The pre-crosslinked gel particles according to any one of claims 1 to 4, characterized in that: The method for preparing the hydroformylated cellulose nanofibrils comprises the following steps: mixing the cellulose nanofibrils, periodate and a solvent to react, and the obtained solid is the hydroformylated cellulose nanofibrils.
6. The pre-crosslinked gel particles according to claim 5, characterized in that: The reaction is carried out under light-proof conditions at a temperature of 40-50° C. for 3-4 hours; The pH of the reaction solution was adjusted to 5-6 to carry out the reaction.
7. The pre-crosslinked gel particles according to claim 5 or 6, characterized in that: The periodate is at least one of sodium periodate and potassium periodate; The solvent is water; The mass ratio of the cellulose nanofibrils to periodate is 10:1.5-2.5; The mass of the cellulose nanofibrils is 3-5 wt % of the total mass of the cellulose nanofibrils and the solvent.
8. The method for preparing the pre-crosslinked gel particles according to any one of claims 1 to 7, comprising the following steps: Acrylamide, trans-resveratrol, aldehyded cellulose nanofibrils and triphenyl phenol polyoxyethylene ether methacrylate are dispersed in water, and an initiator is added under deoxygenated conditions to react to obtain a pre-crosslinked gel.
9. The preparation method according to claim 8, characterized in that: The reaction temperature is 50-60°C; the reaction time is 3-5h; Use nitrogen to deoxygenate; The preparation method also includes the steps of granulating, drying and crushing the obtained pre-crosslinked gel after the reaction.
10. Use of the pre-crosslinked gel particles according to any one of claims 1 to 7 as a profile control and water plugging agent in improving oil and gas field recovery.
Citation Information
Patent Citations
Gel profile control agent for plugging channeling of water-flooding oil reservoir of oil field
CN117487531A
Method for preparing cellulose-based composite film with high strength
CN108484984A
High-temperature-resistant and high-salt-resistant composite gel and preparation method thereof
CN116694310A
composition A BASE DE RESVERATROL OU D'UN DERIVE DE RESVERATROL ET D'HYDROTROPE
FR3045332A1
Process for producing hydrophobically associating polyacrylamides
IN202027018045A